2019
DOI: 10.3329/jbau.v17i3.43200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and diversity studies of yield and yield contributing characters in Brassica genotypes

Abstract: The potential of a crop to favorably respond to breeding programs depends on its existing nature and magnitude of genetic variability, heritability and genetic advance. An experiment was conducted with eighteen Brassica genotypes following Randomized complete block design (RCBD) with three replications at the field of the department of Genetics and Plant Breeding, Bangladesh Agricultural University, Mymensingh, Bangladesh to estimate genetic divergence, variability ranges and contribution of each trait towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 8 publications
6
2
0
Order By: Relevance
“…Higher value of PCV (30.23%) and GCV (29.52%) had also estimated for this trait indicated the existence of inherent variability among the studied genotypes but differences between phenotypic and genotypic variance was relatively higher (124.21) indicated influence of environment (Table 3). The result matched with Aktar et al, (2019), Gupta et al, (2019) and Rout et al, (2019). The genotypic variance (34.42), phenotypic variance (33.52), environmental variance (0.90), high GCV (26.76) and high PCV (27.12) had estimated for number of seeds siliqua -1 (Table 3).…”
Section: Variabilitysupporting
confidence: 87%
See 4 more Smart Citations
“…Higher value of PCV (30.23%) and GCV (29.52%) had also estimated for this trait indicated the existence of inherent variability among the studied genotypes but differences between phenotypic and genotypic variance was relatively higher (124.21) indicated influence of environment (Table 3). The result matched with Aktar et al, (2019), Gupta et al, (2019) and Rout et al, (2019). The genotypic variance (34.42), phenotypic variance (33.52), environmental variance (0.90), high GCV (26.76) and high PCV (27.12) had estimated for number of seeds siliqua -1 (Table 3).…”
Section: Variabilitysupporting
confidence: 87%
“…The PCV and GCV also had the higher values, 25.38 and 25.19 % respectively (Table 3). Iqbal et al, (2015), Naznin et al, (2015) and Aktar et al, (2019) also found the similar results. High PCV and GCV values for this traits had supported by Gupta et al, (2019), indicated the existence of inherent variability among the studied genotypes for this trait.…”
Section: Variabilitysupporting
confidence: 63%
See 3 more Smart Citations